Pre-eclampsia/eclampsia in twin pregnancies. - McFarlane, A (1976)
A study of 1045 twin gestations with regard to known or likely zygosity and the incidence of pre-eclampsia/eclampsia failed to reveal differences between known dizygous twins and like-sex 'presumed' and 'estimated' monozygous twins except in the 'estimated' data for multigravidae. There was a threefold increase in the incidence for twins as opposed to singleton pregnancies. These results are discussed in relation to increased conceptus-mother antigenic differences. It is suggested that the risk of gestosis in twin pregnancy involves more than a summation of that operating in two singleton pregnancies.